2015
DOI: 10.1007/s00464-015-4358-8
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter study of using carbon nanoparticles to show sentinel lymph nodes in early gastric cancer

Abstract: It is feasible to use carbon nanoparticles to show SLNs in early gastric cancer. Carbon nanoparticles suspension is safe for submucosal injection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 29 publications
2
40
0
Order By: Relevance
“…However, no ideal materials have been found due to the limitation of their staining efficiency, the relatively complicated lymphatic flow of the gastric system, radiation injury, and expense. Carbon nanoparticles (CN) are one of the most commonly used nanoparticles to trace LNs in some tumors because they are inexpensive and widely available (43)(44)(45). Recently, LN labeling with CN was applied to GC and can improve the number of RLNs and the detection of MLNs (46).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, no ideal materials have been found due to the limitation of their staining efficiency, the relatively complicated lymphatic flow of the gastric system, radiation injury, and expense. Carbon nanoparticles (CN) are one of the most commonly used nanoparticles to trace LNs in some tumors because they are inexpensive and widely available (43)(44)(45). Recently, LN labeling with CN was applied to GC and can improve the number of RLNs and the detection of MLNs (46).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a more precise oncologic prognostic assessment is provided by increasing the number of RLNs (21.1 vs. 8.0, p < 0.001) using the dye-tracing method. Furthermore, in the CN group, the mean time for LN retrieval was shorter than that in the control group (27.6 vs. 34.6 min, p < 0.001) (45). Li et al conducted a prospective randomized trial to evaluate the efficiency and safety of CN for retrieving LNs in advanced GC (47).…”
Section: Discussionmentioning
confidence: 99%
“…10,11 The reason is that CNPs cannot enter the blood vessel and cause systemic adverse reactions. 10,11 Studies about CNPs in breast cancer, endometrial cancer, and gastric cancer have not reported adverse reactions, [18][19][20] while adverse reactions such as allergic reactions, pruritus, and rashes are reported when using the blue dye. 15,16 In recent years, ICG fluorescence has been the main recommended method in studies, among which the prospective FILM trial reported an overall detection rate of 98%.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous study, lymphatic fondness of CNs were benefit from not only its special molecular structure but also phagocytosed by macrophage [19]. Furthermore, the long-term staining and tracing of CNs provide a feasible technique to explore the relationship between lymphovascular invasion and the regression of positive nodes.…”
Section: Discussionmentioning
confidence: 99%